Association of serum homocysteine levels with the development of preeclampsia - Kannayan, Lokeshwari; Shamim, Nazma; Arpana, Anju; Mudigubba, Manoj Kumar; B, Sreenivasa (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To determine the association between serum homocysteine levels and preeclampsia and its relevance as a potential marker for predicting preeclampsia. Methods: A total number of 50 preeclampsia cases were taken. 30 cases of normal pregnancy were taken as controls. This study was carried out in the Department of Obstetrics and Gynecology, Gauhati Medical College and Hospital, Gauahati from August 2012 to July 2013. Blood samples were drawn from the antecubital vein and serum homocysteine levels were measured. Results: The mean serum homocysteine levels in preeclampsia cases were 27.7 ± 6.4 μmol/l compared to serum homocysteine levels in normal pregnancy 9.23 ± 3.4 μmol/l (P<0.01).There was a significant relationship between the systolic and the diastolic blood pressure and serum homocysteine levels. As the systolic and diastolic blood pressure increases, serum homocysteine levels also increased significantly (P<0.001). Conclusion: This study showed raised serum homocysteine levels in patients with preeclampsia compared to normal pregnancy. Keywords: Serum homocysteine; Preeclampsia; Blood pressure